Howard the Duck - Huyck, Willard; Thompson, Lea, 1961-; Jones, Jeffrey, 1947-; Robbins, Tim, 1958- (Universal City, Calif. : Universal, 2009)
The outrageous film about a highly-evolved offbeat duck from outer space. Based on the popular Marvel Comics. Follow the exploits of a wise-cracking, cigar-chomping duck as he tries to return to his home planet.
Originally released as a motion picture in 1986.
Presented in widescreen format.
Special features: "A look back at Howard the Duck"; releasing the duck; news featurette; the stunts of Howard the Duck; the special effects of Howard the Duck; the music of Howard the Duck; teaser trailers.
Director of photography, Richard H. Kline ; executive producer, George Lucas.
Lea Thompson, Jeffrey Jones, Tim Robbins.
MPAA rating: PG.
Keywords: Extraterrestrial beings; Human-alien encounters; Comedy films; Science fiction films; Video recordings for the hearing impaired; Feature films